TINJAUAN YURIDIS TERHADAP PROSES PENYELESAIAN KASUS KECELAKAAN LALU LINTAS MELALUI ADR (ALTERNATIF DISPUTE RESOLUTION) DI WILAYAH HUKUM POLDA JATIM - M Syifa Yulianis (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2022)
Traffic accidents that occur a lot are very regrettable, especially since there have been many rules given, there are several things why there are many accidents on the road, one of which is the low ethics of driving on the road, as well as the lack of road users and the disobedience of road users to all traffic rules so the biggest factor is the factor of human negligence, with the occurrence of traffic accidents will cause casualties from minor injuries, severe injuries to loss of life, all of which require a fair solution for both parties, and one of the solutions that can be applied to cases of road accidents is to use peaceful roads or through arlternative dispute resolution (ADR), the research method used is normative research methods with a statutory approach as the main legal material, a review based on legal norms that cover many things including how investigators' efforts in resolving traffic accident cases through ADR (Alternative Dispute Resolution) and what factors abort the validity of the settlement of traffic accident cases through ADR (Alternative Dispute Resolution).